2011
DOI: 10.1177/0095244311425998
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the processing parameters in melt blending of thermoplastic polyurethane and poly dimethyl siloxane rubber

Abstract: This article emphasizes the optimization of processing parameters required for the blending of polyether-based thermoplastic polyurethane (TPU) and poly dimethyl siloxane (PDMS) rubber. Taguchi methodology was adapted as a statistical tool in the design of experiment to optimize processing conditions on the basis of tensile strength and impact strength for 50:50 blend of TPU and PDMS. L 9 (3 3 ) orthogonal array strategy was utilized for conducting the experiments. The experimental data were transformed into s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…PDMS is another class of material which is growing in tandem with TPU in terms of biological applications due to its unique biocompatibility . This has led to the development of TPU–PDMS blends by exploring the synergistic effects . However, TPU–PDMS blend is a heterogeneous system and therefore it manifests as an unstable two‐phase morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PDMS is another class of material which is growing in tandem with TPU in terms of biological applications due to its unique biocompatibility . This has led to the development of TPU–PDMS blends by exploring the synergistic effects . However, TPU–PDMS blend is a heterogeneous system and therefore it manifests as an unstable two‐phase morphology.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] This has led to the development of TPU-PDMS blends by exploring the synergistic effects. [15][16][17][18][19] However, TPU-PDMS blend is a heterogeneous system and therefore it manifests as an unstable two-phase morphology. The selection of blending technique, as well as compatibilization method in such systems is crucial to obtain maximum synergy.…”
Section: Introductionmentioning
confidence: 99%
“…Blends of TPU and PDMS were prepared in a Brabender Plastograph1 EC (digital 3.8-kW motor, a torque measuring range of 200 Nm, at a speed range from 0.2 to 150 min À1 ) per the procedure established in an earlier publication. 10 TPU was allowed to melt at 190 C after which the unmodified n-HA/PPG-modified n-HA was added to it, and the blend was mixed in the plastograph for two more minutes. At the next stage, PDMS was added and melt blended for another 3 min in the plastograph.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…In the earlier works, the authors have shown that the blends of TPU and PDMS rubber develop the desired phase morphology by controlling the processing parameters and also through in-situ compatibilization to achieve improved mechanical strength properties suitable for biomedical applications. [10][11][12][13] In the present study, the authors have attempted to investigate the synthesis and characterization of HA nanorods and the preparation of n-HA composites derived from TPU-PDMS immiscible blends. The surface of the n-HA nanorods was modified with polypropylene glycol (PPG) to enhance the interaction with the polymer matrices to achieve good mechanical strength, good stiffness, and flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…This motivated us to investigate further on optimizing the process parameters for EMA/NBR blends. Taguchi technique employs a unique devise of orthogonal arrays to cover the entire blend mixing conditions with the least number of experiments . Application of Taguchi methodology in the optimization of processing variables during melt polymer mixing of diverse polymer blend systems has been reported in the literature .…”
Section: Introductionmentioning
confidence: 99%